The rise and fall of post-liberal regionalism: Between ideological convergence and regional leadership - Alvarez, María Victoria (Faculdade de Ciências e Letras - Unesp - Araraquara., 2021)
A decade after the rise of post-liberal regionalism, strong movements are emerging to the detriment of their survival, both in the case of UNASUR and ALBA. What factors explained the emergence of these post-liberal regionalism schemes? Can the weakening of these factors explain the current exhaustion of this wave of regionalism? We assume that ideological convergence and regional leadership are facilitators of regionalism. However, we conjecture that ideological affinity by itself cannot account for variable patterns in regional cooperation. Especially in the period of post-liberal regionalism, Brazil’s and Venezuela’s will (with Presidents Lula da Silva and Hugo Chávez) to lead was central, and therefore, both the emergence and the decline of ALBA and UNASUR can be explained predominantly by the swings of regional leadership.